The politics of imprisonment how the democratic process shapes the way America punishes offenders - Barker, Vanessa (New York ; Oxford : Oxford University Press, 2009)
'The Politics of Imprisonment' examines how the democratic process and social trust shape penal sanctioning in the United States. Drawing on a range of archival sources, Barker shows that higher levels of civic engagement tend to support milder punishments whereas lower levels tend to support more coercive criminal justice policies.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Criminal justice, Administration of -- United States -- States; Criminals -- United States -- States; Imprisonment -- United States -- States; Equality -- United States -- States; Discrimination in criminal justice administration -- United States -- States